Effects of Source Credibility and Short Video Platform Quality on Tourist Attitudes and Travel Intention: Moderating Role of Parasocial Interaction - Almanda Tomatala; Heppy Millanyani; Vigory Manulu (Jurnal Ragam Pengabdian, 2026)
Short video platforms have become important digital spaces for accessing travel information and shaping tourism-related intentions. In Indonesia, tourism content on TikTok, Instagram Reels, YouTube Shorts, and Facebook Reels continues to expand, yet the combined influence of social and technological factors on tourists’ attitudes remains underexplored. This study examines the effects of source credibility and short video platform quality on tourists’ attitudes and travel intention, as well as the moderating role of parasocial interaction. A quantitative approach was employed through an online survey of Indonesian users who had watched tourism-related short videos. A total of 351 valid responses were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that perceived expertise and perceived trustworthiness significantly influence attitude toward destination, whereas perceived attractiveness has no significant effect. Perceived usefulness, perceived ease of use, and perceived enjoyment significantly influence attitude toward short video platforms. Both attitude toward destination and attitude toward short video platforms positively affect travel intention. However, attitude toward short video platforms does not affect attitude toward destination, and parasocial interaction does not moderate the relationship between source credibility and attitude toward destination. These findings emphasize the importance of credible tourism information and positive platform experiences in enhancing travel intention.